Individual differences in growth and in accumulation of secondary metabolites in Rhodiola rosea cultivated in Western Siberia - Erst, Anna A.; Kotsupiy, Olga V.; Erst, Andrey S.; Kuznetsov, Alexander A. (International journal of molecular sciences)
In this study, growth parameters of underground parts and concentrations of phenylpropanoids, phenylethanoids, flavonoids, hydroxybenzoic acids, and catechins in aqueous-ethanol extracts of 6-year-old cultivated plants of Rhodiola rosea (propagated in vitro) of Altai Mountain origin were analyzed, and differences in chemical composition among plant specimens and between plant parts (rhizome and root) were evaluated. High-performance liquid chromatography detected 13 phenolic compounds. Roots contained 1.28 times higher phenylethanoids levels (1273.72 mg/100 g) than rhizomes did. Overall, the concentration of phenylethanoids in underground organs was not high and ranged from 21.36 to 103.00 mg/100 g. High variation among R. rosea individual plants was noted both in growth characteristics and in levels of secondary metabolites under our cultivation conditions. It was found that concentrations of phenylpropanoids, phenylethanoids, and catechins significantly depend on the plant part analyzed (p ≤ 0.05). Specimen No. 4 is characterized by the highest concentration of rosavins (1230.99 mg/plant) and the lowest concentration of cinnamyl alcohol (62.87 mg/plant). Despite the wide range of values, all 10 tested specimens (underground part) met the minimum requirements of the United States Pharmacopeia (2015) for rosavins (0.3%) and of the Russia State Pharmacopoeia (2015) for the average level of rosavins (roots): (1%).